2015
DOI: 10.1167/iovs.14-16158
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of MitochondrialND4Mutations in 1281 Han Chinese Subjects With Leber's Hereditary Optic Neuropathy

Abstract: These results suggested that the ND4 gene is the hot spot for mutations associated with LHON. Thus, these findings may provide valuable information for the further understanding of pathogenic mechanism of LHON.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 59 publications
0
42
1
1
Order By: Relevance
“…Mutations of the multi-gene panel were designed from the Mitomap database, previous reports and our previous study in a Chinese Han population (8)(9)(10). Twenty-seven amplicons, the specific primers for the point mutations, covered those of 46 mutations, as well as other substitutions in the amplicons, such as pathogenic mutations, m.3697G>A, m.10197G>A and m.14459G>A in the fragments of amplicon 4, 13 and 23, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mutations of the multi-gene panel were designed from the Mitomap database, previous reports and our previous study in a Chinese Han population (8)(9)(10). Twenty-seven amplicons, the specific primers for the point mutations, covered those of 46 mutations, as well as other substitutions in the amplicons, such as pathogenic mutations, m.3697G>A, m.10197G>A and m.14459G>A in the fragments of amplicon 4, 13 and 23, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 275 unrelated LHON samples and 281 Chinese control samples were enrolled from the ophthalmology clinics at Zhejiang University School of Medicine (Hangzhou, China) and Wenzhou Medical College (Wenzhou, China) between 2004 and 2015, as described previously (8)(9)(10)12), under protocols approved by Zhejiang University and Wenzhou Medical University Ethics Committees. DNA was extracted from 1 ml peripheral blood using a QIAamp DNA Blood Minikit (51106; Qiagen China Co., Ltd., Shanghai, China).…”
Section: Dna Samples Extraction Quantification and Quality Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…7,19,20 In this cohort, 503 probands had a family history of optic neuropathy, and 778 subjects were sporadic cases. 7 Mutational analysis showed that mutations in MT-ND4 and MT-ND6 genes are responsible for 39.5% and 9.3% cases of LHON subjects in this large cohort, respectively. 7,19 In the present study, we carried out a systematic and extended mutational screening of the MT-ND1 gene in a cohort of 1281 genetically unrelated Han Chinese subjects with LHON.…”
mentioning
confidence: 76%